Editorial - Zeta de Pozo, Rosa (2018)
We present the second edition of the Revista de Comunicacion included on the Scopus Database. With this guarantee we assume the challenge of maintaining quality and prioritizing the relevant themes of communication, as a changing reality, with essence and social transcendence. The rhythm of change continues. New and emerging technologies like artificial intelligence and virtual reality continue to redefine the field of communication. However they’re not everything. The last forecast from the North American consultancy firm PriceWaterhouse Coopers, “The Global Entertainment-Media Outlook 2018-2022”, predicts that convergence 3.0, connections and trust are trending for this 5 year period. For future success, they say, appropriate technologies, and excellent content, delivered at a cost-effective level will be needed to engage that audience that already relies on media and entertainment companies. We affirm that trust is becoming a vital differentiator in the digital world.